Motivation as An Intervening Variables Influence Competency on the Performance of Cooperative Managers - Eko Nur Fu'ad; Moch. Aminnudin (Journal of Management and Entrepreneurship Research, 2020)
Objective: This paper discussed the importance of competence and work motivation, and analysed the effect of these two variables on performance. Research Design & Methods: This research sought to understand more about the manager’s performance of microfinance institutions (cooperatives), so the selected sample was cooperative managers. The data collected from 88 questionnaires were analysed using PLS-SEM with SMART-PLS software. Findings: Competence has a significant effect on motivation and manager performance, motivation has a significant effect on performance, motivation as an intervening variable on the effect of competence on performance. Implications & Recommendations: Work motivation is a more influential factor than competence on performance, so the activity that must be done to improve performance is to improve work motivation. Subsequent research carried out in other industries or with a larger sample size for generalization purposes. Contribution & Value Added: The main contribution of this research is that to increase work motivation, it can be done by requiring employees to always improve their past performance for the better.